Reformation From Within: A Contemporary Dynamics of Muhammadiyah Intellectuals in the Early 21st Century - Khoirun Niam; Syamsul Arifin (Al-Jami'ah: Journal of Islamic Studies, 2025)
This article seeks to trace how Muhammadiyah cultivates its Muslim intellectuals, particularly in the early 21st century, and examines how their contributions promote intellectual and charitable initiatives. Through interviews with prominent Muhammadiyah leaders and scholars, as well as documentary research, the article reveals that the emergence of Muhammadiyah intellectuals in the early twenty-first century is rooted in two types of educational institutions. The first group consists of those who completed their education at pesantren, while the second comprises individuals educated within the national school system who also graduated from higher education institutions. Social and political conditions further contributed to the formation of Muhammadiyah intellectuals. The large number of Muhammadiyah charities has led to criticism that Muhammadiyah intellectual thought is stagnant. Their focus has largely been directed toward supporting regular and tangible organizational activities, including humanitarian efforts, social initiatives, and educational programs, among others. [Artikel ini menelusuri upaya Muhammadiyah membina intelektual Muslimnya, khususnya pada awal abad ke-21, serta mengkaji kontribusi mereka yang mendorong inisiatif keilmuan dan filantropis. Berdasarkan wawancara dengan tokoh dan cendekiawan terkemuka Muhammadiyah serta penelitian dokumen, tulisan ini mengungkap bahwa kemunculan intelektual Muhammadiyah pada awal abad ke-21 berakar pada dua jenis lembaga pendidikan: pertama, mereka yang menempuh pendidikan di pesantren dan, kedua, mereka yang memperoleh pendidikan melalui sistem sekolah nasional dan melanjutkan ke jenjang pendidikan tinggi. Kondisi sosial dan politik juga turut memengaruhi terbentuknya para intelektual Muhammadiyah. Banyaknya amal usaha Muhammadiyah memunculkan kritik bahwa pemikiran intelektual Muhammadiyah mengalami stagnasi. Fokus para intelektual Muhammadiyah lebih diarahkan untuk mendukung aktivitas organisasi yang bersifat rutin dan nyata, seperti kegiatan kemanusiaan, inisiatif sosial, dan program-program pendidikan.]